(untitled) (Tidsskrift for Praktisk Teologi, 2020)
Discussing the contribution of Learning and knowledge trajectories in congregations (LETRA) is a challenge, particularly when one was involved in it. Two research questions are posed: How has the methodological and theoretical framework of LETRA contributed to knowledge about learning in congregations? What are the differences between LETRA and related Norwegian research projects within practical theology? The first part presents key features of the three different strains of theory within LETRA, and brief examples of how researchers in LETRA have utilized them. The second part discusses the research contribution of LETRA on two topics, “object” and “materiality”, taking articles by other researchers as vantage points. The article concludes that LETRA has contributed to scientific novelty through its combination of an empirical descriptive design and a pool of practice theories. However, novelty is a moving target. It is necessary to continually pursue theoretical openness in order to conduct empirical research on congregational and religious change in societiy.